2012 XXXVIII Conferencia Latinoamericana en Informatica (CLEI) 2012
DOI: 10.1109/clei.2012.6427197
|View full text |Cite
|
Sign up to set email alerts
|

Software inspection adoption: A mapping study

Abstract: In Software Engineering technical literature the references about the benefits of software inspections are abundant. In contrast, some authors raise the problem of low adoption of this process. From this issue a literature review is made to produce a map on most researched topics in the area, factors causing low adoption and possible solutions. Results showed a list of 64 articles selected using a search protocol, which were classified according to a defined taxonomy. The founded factors were codified and a li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 30 publications
0
14
0
3
Order By: Relevance
“…In this section, we first discuss the motivations and guiding ideas that have inspired our proposal. Then, we will discuss the role and relevance of meeting in software inspection.Scarce implementation of inspection processes: We have performed an exhaustive literature survey, obviously supported by existing previous surveys and systematic literature reviews , especially the most recent ones . Macchi and Solari concluded that low adoption of the inspection process is induced by several factors including developers' perceptions about the process, lack of training, characteristics of the process – such as complexity and so on.…”
Section: Need For a Practical Inspection Process: Evaluation Of Softwmentioning
confidence: 94%
See 3 more Smart Citations
“…In this section, we first discuss the motivations and guiding ideas that have inspired our proposal. Then, we will discuss the role and relevance of meeting in software inspection.Scarce implementation of inspection processes: We have performed an exhaustive literature survey, obviously supported by existing previous surveys and systematic literature reviews , especially the most recent ones . Macchi and Solari concluded that low adoption of the inspection process is induced by several factors including developers' perceptions about the process, lack of training, characteristics of the process – such as complexity and so on.…”
Section: Need For a Practical Inspection Process: Evaluation Of Softwmentioning
confidence: 94%
“…Then, we will discuss the role and relevance of meeting in software inspection.Scarce implementation of inspection processes: We have performed an exhaustive literature survey, obviously supported by existing previous surveys and systematic literature reviews , especially the most recent ones . Macchi and Solari concluded that low adoption of the inspection process is induced by several factors including developers' perceptions about the process, lack of training, characteristics of the process – such as complexity and so on. In the study of Kollanus and Koskinen , these authors suggested performing more empirical studies for better understanding of inspection process in different types of organisations and environments.We have identified and selected two major issues in SI‐related literature (on which we have worked).…”
Section: Need For a Practical Inspection Process: Evaluation Of Softwmentioning
confidence: 94%
See 2 more Smart Citations
“…For instance, Wheeler et al [54] presented interesting information regarding the use of inspections in the industry (Table I) in the 90´s. Surprisingly, software industry (in general) still does not make large use of software inspections despite all their benefits [12] [34].…”
Section: Introductionmentioning
confidence: 98%